Artikel Upaya Peningkatan Kesadaran Masyarakat terhadap Bahaya Judi online dan Pinjaman online melalui Penyuluhan Kelompok 74 KKN UIN SMH Banten di Kampung Simangu: Judi Online, Penyuluhan Hukum, Pinjaman Online - Hikmatullah; Nurfitriyani; Selvy Anugrah Maharani; Diah Ayu Suciyati; Amira Sohwa Azzahra; jumaedi medi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
Online gambling (judol) and illegal online loans (pinjol) are two negative phenomena that have rapidly grown in the digital era. Judol involves online betting with the promise of quick profits, but often results in financial loss, addiction, and social disruption. Illegal pinjol offer easy, unsecured loans with high interest rates and aggressive collection efforts that harm borrowers and misuse personal data. Both practices have serious economic, social, and psychological impacts, especially for less educated communities and those experiencing financial difficulties. To address these issues, legal education and outreach are crucial to increase public understanding of the dangers and regulations related to illegal judol and pinjol. Students from the 74th batch of the UIN SMH Banten Community Service Program (KKN) conducted outreach in Pageragung Village, Walantaka, with the aim of equipping teenagers and parents to recognize operational methods, avoid pitfalls, and play an active role in reporting illegal practices. These efforts are expected to strengthen legal awareness and community socioeconomic resilience, thereby creating a safer, healthier, and more productive environment in facing the challenges of digital technology.